The bodemeyeri and the convexicollis species groups of the genus Geodromicus Redtenbacher, 1857, and additional taxonomic and faunistic data for some species of the Eastern Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2022)
Two new species-group are established for the Palaearctic species of the Geodromicus Redtenbacher, 1857: the bodemeyeri-group containing G. (s.str.) bodemeyeri Bernhauer, 1902 (Russia (Caucasus), Turkey), G. (s.str.) championi Cameron, 1924 (Pakistan, India, Nepal) and G. (s.str.) zwickianus Fagel, 1976 (Turkey, Iran); the convexicollis-group containing G. (s.str.) convexicollis Luze, 1903 (Middle Asia), G. (s.str.) kashmirensis Cameron, 1930 (Afghanistan, Pakistan, India), G. (s.str.) lebedevianus Roubal, 1929 (Kyrgyzstan), G. (s.str.) macrothorax Kashcheev, 1999 (Kazakhstan, Kyrgyzstan), G. (s.str.) malcolmi sp.n. (India: Uttarakhand) and G. (s.str.) medvedevi Shavrin, 2009 (Pakistan). All these species are (re-)described (except of G. (s.str.) medvedevi) and illustrated. The neotype for G. lebedevianus is designated. Keys to species of the bodemeyeri-group and the convexicollis-group are provided. Five species from the Himalayan Region are redescribed and illustrated: G. (s.str.) affinis Cameron, 1934 and G. (s.str.) alticola Cameron, 1945 (both from Pakistan, India), G. (s.str.) curvipes Cameron, 1924 (India, Nepal), G. (s.str.) ruficornis Cameron, 1941 (India: Kashmir) and G. (s.str.) subsimilis Cameron, 1941 (India, Nepal). Aedeagi for G. (s.str.) curvipes and G. (s.str.) subsimilis are figured for the first time. The following new synonymies are established: G. (s.str.) bodemeyeri = G. convexus Iablokoff-Khnzorian, 1962 syn.n., = G. (s.str.) rivularis Iablokoff-Khnzorian, 1962 syn.; G. (s.str.) championi = G. nepalicus Coiffait, 1977 syn.n.; G. (s.str.) convexicollis = G. cylindricus Tronquet, 1981 syn.n.; G. (s.str.) kashmirensis = G. similis Cameron, 1930 syn.n., = G. consors Cameron, 1945 syn.n., = G. afghanicus Scheerpeltz, 1961 syn.n., = G. karakorus Coiffait, 1977 syn.n.; G. (s.str.) affinis = G. torrentis Puthz, 1973 syn.n.; G. (s.str.) alticola = G. peraffinis Cameron, 1945 syn.n., = G. brancuccii Coiffait, 1984 syn.n. Lectotypes are designated for: G. championi, G. kashmirensis, G. similis and G. curvipes. Distribution maps for all species are provided. Geodromicus (s.str.) championi and G. (s.str.) subsimilis are recorded from Pakistan and Nepal respectively for the first time. Additionally, faunistic records of five species from the Eastern Palaearctic Region are provided. The habitus of G. (s.str.) medvedevi and G. (s.str.) smetanai Shavrin, 2018 are illustrated for the first time.